GAMBARAN TINGKAT DEPRESI PADA WANITA PEKERJA SEKS DI KALANGAN REMAJA DI KOTA MANADO - Wardoyo, Serly; Kaunang, Theresia M. D.; Munayang, Herdy (Universitas Sam Ratulangi, 2014)
Abstract: Depression is a mental disorder that is predicted by the World Health Organization which will be ranked first in the burden of disease on a global scale in 2030. Emotional maturity of the teens which is still unstable, highly susceptible to depression. Especially for those who work as female sex workers and often receive negative pressure when they work. Method: This research is a descriptive study with cross-sectional design. Depression among 30 adolescent FSWs will be assessed using the Beck Depression Inventory II questionnaire. Results: Results showed that 10.0% FSWs are normal, 30.0% FSWs have mild depression, 36.7% FSWs have moderate depression and 23.3% FSWs have severely depression. Keywords: Depression, Female Sex Worker, adolescent, Beck Depression Inventory. Abstrak: Depresi merupakan gangguan mental yang diprediksikan oleh World Health Organization kelak menduduki peringkat pertama beban penyakit dalam skala global pada tahun 2030. Usia remaja yang kematangan emosionalnya masih labil, sangat rentan mengalami depresi. Apalagi bagi remaja yang berprofesi sebagai Wanita Pekerja Seks yang kerap mendapat berbagai tekanan negatifdalam pekerjaannya. Metode: Penelitian ini bersifat deskriptif dengan desain penelitian cross-sectional. Tingkatan depresi pada 30 remaja WPS akan dinilai dengan menggunakan kuesioner Beck Depression Inventory II. Hasil: Didapatkan sebanyak 10.0% WPS normal, 30.0% WPS mengalami depresi ringan, 36.7% WPS mengalami depresi sedang dan 23.3% WPS mengalami depresi berat. Kata Kunci: Depresi, Wanita Pekerja Seks, remaja, Beck Depression Inventory.